Failure analysis of electric motor due to excessive shaft load using the FMEA method in rice milling units - Sunaryo Sunaryo; Wisnu Yogi Pangestu; Abrar Ridwan (Politeknik Negeri Lhokseumawe, 2026)
While Failure Mode and Effect Analysis (FMEA) has been widely applied in heavy industries, its application in the mid-scale agro-industrial sector remains highly limited. This study addresses this critical gap by analyzing the mechanical failure of electric motors in Rice Milling Units (RMUs) within the Lappariaja District, focusing specifically on the synergistic impact of excessive shaft loading and high-particulate environments on motor longevity. Adopting a descriptive quantitative approach, this research integrates multi-modal data collection, including field observations, technical measurements using digital multimeters, and operator interviews. The FMEA framework was applied to calculate the Risk Priority Number (RPN) for each prominent failure mode. The empirical findings reveal that the Stator Winding is the most critical vulnerability, with the highest RPN of 252, due to a severe